Analisis Kalsium (Ca) pada Ikan Petek dan Mujair dengan Metode Kompleksometri - Azmalina Adriani; Fauziah Fauziah; Riki Saputra (Oceana Biomedicina Journal, 2019)
Fish is one of the example of a comestibles that contains a lot of protein and minerals, one ofwhich is calcium. Calcium functions for the body's metabolism in the bone and toothformation. Petek and Mujair fish contain calcium that is needed by the human body.The purpose of this study was to determine the levels of calcium contained in Petek andMujair fish.The sampling was done by purposive sampling, which the sample used was obtained by themarket in the Peunayong Banda Aceh. This research used complexometry methods. Thesamples of Petek and Mujair fish that had been cleared were titrated using Na2-EDTA as thetitrator.The result showed that Petek and Mujair fish had different calcium levels where the calciumlevels in Petek fish reach an average of 0.853% and the calcium levels in Mujair fish reachan average of 0.616%. Petek fish had higher calcium levels than Mujair fish, it was causedby their habit, where Petek fish was sea fish that contained fat, vitamins and minerals, whileMujair fish was freshwater fish that contained carbohydrates and proteins.